Minicircle Biopharmaceuticals–An Overview of Purification Strategies - Alves, Cláudia P. A.; Prazeres, Duarte Miguel F.; Monteiro, Gabriel A. (Frontiers in Chemical Engineering, 2021)
Minicircles are non-viral delivery vectors with promising features for biopharmaceutical applications. These vectors are plasmid-derived circular DNA molecules that are obtained in vivo in Escherichia coli by the intramolecular recombination of a parental plasmid, which generates a minicircle containing the eukaryotic therapeutic cassette of interest and a miniplasmid containing the prokaryotic backbone. The production process results thus in a complex mixture, which hinders the isolation of minicircle molecules from other DNA molecules. Several strategies have been proposed over the years to meet the challenge of purifying and obtaining high quality minicircles in compliance with the regulatory guidelines for therapeutic use. In minicircle purification, the characteristics of the strain and parental plasmid used have a high impact and strongly affect the purification strategy that can be applied. This review summarizes the different methods developed so far, focusing not only on the purification method itself but also on its dependence on the upstream production strategy used.